Pengaruh PAD, DAU, DAK, dan DBH terhadap Indeks Pembangunan Manusia di Indonesia - Cahya Fahma Arrosyid; Andy Dwi Bayu Bawono (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The provincial government is granted autonomy to manage regional wealth with the aim of developing public facilities and infrastructure that support community welfare. Such development is directed at improving the Human Development Index (HDI) as a reflection of quality human resources. This study investigates the influence of Regional Original Income (PAD), General Allocation Funds (DAU), Special Allocation Funds (DAK), and Revenue Sharing Funds (DBH) on provincial HDI in Indonesia. A quantitative research method was employed using hypothesis testing. The study population consists of all provincial budget realization reports, while the sample includes 34 provinces that submitted reports for the 2017–2018 fiscal years. The sample was selected using a saturated sampling technique, and data were collected through documentation and literature. Analytical techniques included panel data regression, preceded by classical assumption tests, the F-test, R² test, and t-test. The findings reveal that PAD has a positive and significant impact on HDI, as it is mostly allocated for capital and operational expenditures that enhance welfare. Conversely, DAU, DAK, and DBH show no significant effect on HDI, since their allocations are limited in supporting facilities and infrastructure development. These results highlight the crucial role of PAD in improving human development outcomes at the provincial level.